RELATION BETWEEN FOOD CONSUMPTION PATTERN OF RISK, FRUIT AND VEGETABLE CONSUMPTION AND HEART DISEASE EVENTS AGE OF 45-59 YEARS IN SULAWESI ISLAND (DATA ANALYSIS OF RISKESDAS 2007) - Alifiyanti, Muharramah; Iskari, Ngadiarti; Sri, Hartati Lilik (Jurnal Nutrire Diaita (Ilmu Gizi), 2016)
AbstractBackground: The prevalence of heart disease events in Indonesia in 2007 is 0,9%, while on the island of Sulawesi is 2,1%. Nationally, the prevalence of people with risky food consumption over 45 years of age showed 66,3% consumption of sweet foods, salty foods consumption of 24,9%, 12,5% consumption of fatty foods, 1,8% consumption of offal. This is also reflected in the prevalence of Indonesia's population who consume less fruit and vegetables at the age of 45 years showed that 93,5% (Riskesdas, 2007). Objective: To determine the relationship of food consumption patterns and the risk of fruit and vegetable consumption and the incidence of heart disease aged 45-59 years in Sulawesi island. Methods: Samples were obtained 17099 respondents of age 45-59 years from the data Riskesdas 2007. Data were analyzed using chi-square test and multiple logistic regression. Results: The percentage of events heart disease at the age of 45-59 years amounted is 2.1% of Sulawesi Island. Based on the results of the bivariate test related to the incidence of heart disease is the pattern of consumption of salty foods (p = 0.000) and consumption of fruit (p= 0.019), whereas that is not related to the incidence of heart disease is the pattern of consumption of sweet foods (p= 0.632), fat (p= 0.287), offal (p= 0.757), and vegetable consumption (p= 0.576). Based on the results of multivariate analysis the most effect on the incidence of heart disease is often salty food consumption patterns with OR 2.150. Conclusion: Need to do counseling activities about the dangers of consuming salty foods above the standards prescribed because it can affect the health of non-communicable diseases especially like heart disease and other factors that can lead to heart disease.Keywords : Patterns of foodfruit and vegetable consumption, heart disease.Â AbstrakLatar Belakang : Prevalensi kejadian penyakit jantung di Indonesia tahun 2007 sebesar 0,9% sedangkan di Pulau Sulawesi sebesar 2,1%. Secara nasional prevalensi penduduk dengan konsumsi makanan berisiko usia diatas 45 tahun menunjukkan 66,3% konsumsi makanan manis, 24,9% konsumsi makanan asin, 12,5% konsumsi makanan berlemak, 1,8% konsumsi jeroan. Hal tersebut juga terjadi pada prevalensi penduduk Indonesia yang kurang mengkonsumsi buah dan sayur pada usia 45 tahun menunjukkan 93,5% (Riskesdas, 2007). Tujuan : Mengetahui hubungan pola konsumsi makanan berisiko dan konsumsi buah dan sayur dan kejadian penyakit jantung usia 45-59 tahun di Pulau Sulawesi. Metode Penelitian : Sampel yang didapat 17099 responden usia 45-59 tahun dari data Riskesdas 2007. Analisis data menggunakan Uji Chi-square dan Uji Regresi Logistik Ganda. Hasil Penelitian: Persentasi kejadian penyakit jantung usia 45-59 tahun di Pulau Sulawesi sebesar 2,1%. Berdasarkan hasil uji bivariat yang berhubungan terhadap kejadian penyakit jantung yaitu pola konsumsi makanan asin (p=0,000) dan konsumsi buah (p=0,019), sedangkan yang tidak berhubungan terhadap kejadian penyakit jantung yaitu pola konsumsi makanan manis (p=0,632), berlemak (p=0,287), jeroan (p=0,757), dan konsumsi sayur (p=0,576). Berdasarkan hasil uji multivariat yang paling berpengaruh terhadap kejadian penyakit jantung adalah pola konsumsi makanan asin sering dengan OR 2,150. Kesimpulan: Perlu dilakukan kegiatan penyuluhan mengenai bahaya mengkonsumsi makanan asin di atas standar yang sudah ditentukan karena dapat berpengaruh pada kesehatan terutama penyakit tidak menular seperti penyakit jantung dan faktor lainnya yang dapat mengakibatkan terjadinya penyakit jantung.Kata Kunci : Pola konsumsi, konsumsi buah dan sayur, penyakit jantung